2015
DOI: 10.1007/s11010-015-2456-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluorofenidone protects against renal fibrosis by inhibiting STAT3 tyrosine phosphorylation

Abstract: Signaling through the Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway, especially JAK2/STAT3, is involved in renal fibrosis. Fluorofenidone (FD), a novel pyridone agent, exerts anti-fibrotic effects in vitro and in vivo. Herein, we sought to investigate whether FD demonstrates its inhibitory function through preventing JAK2/STAT3 pathway. In this study, we examined the effect of FD on activation of rat renal interstitial fibroblasts, glomerular mesangial cells (GMC), and expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
(64 reference statements)
3
11
0
Order By: Relevance
“…Previous studies showed that renal inflammation played an important role in the development of renal fibrosis . AKF‐PD, a novel low‐molecular‐weight pyridine agent, exerts strong anti‐fibrotic effect . In this study, we found that treatment with AKF‐PD reduced the deposition of collagens and attenuated kidney interstitial fibrosis in UUO.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous studies showed that renal inflammation played an important role in the development of renal fibrosis . AKF‐PD, a novel low‐molecular‐weight pyridine agent, exerts strong anti‐fibrotic effect . In this study, we found that treatment with AKF‐PD reduced the deposition of collagens and attenuated kidney interstitial fibrosis in UUO.…”
Section: Discussionsupporting
confidence: 54%
“…2 AKF-PD, a novel low-molecular-weight pyridine agent, exerts strong anti-fibrotic effect. [27][28][29][30] In this study, we found that treatment with AKF-PD reduced the deposition of collagens and attenuated kidney interstitial fibrosis in UUO. Furthermore, AKF-PD treatment significantly ameliorated UUO-induced leukocytes infiltration.…”
Section: Discussionsupporting
confidence: 53%
“…Just as previously described, the JAK2/STAT3 pathway may contribute to the progression of renal interstitial fibrosis [12, 18]. Many drugs attenuate renal fibrosis by targeting the JAK2/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 89%
“…Many drugs attenuate renal fibrosis by targeting the JAK2/STAT3 pathway. It has been indicated that fluorofenidone protects against renal fibrosis by inhibiting STAT3 tyrosine phosphorylation [12]. And Zhang et al[8] found that Paclitaxel attenuates renal interstitial fibroblast activation and interstitial fibrosis by inhibiting STAT3 signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation